1982
DOI: 10.1021/ac00244a041
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sub-parts-per-billion levels of acrylonitrile in aqueous solutions

Abstract: A method combining steam distillation, elevated-temperature purge-and-trap, and nitrogen-specific detection has been developed for detection of low and sub-parts-per-billion levels of acrylonitrile in aqueous systems. Steam distillation effects a sample cleanup and concentrates acrylonitrile. Combination of the elevated purge-and-trap technique with a thermal N-P detector provides selective and sensitive detection. The method has been validated for acrylonitrile In water over the range of 10 ppt to 10 ppb. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The lack of a statistically significant difference between the mean of the normalized data collected at the beginning of a 6-month analysis period and the overall mean of all analyses over 6 months strongly suggests the following: (1) The analytical system was relatively constant in performance in spite of daily tuning, calibration, and other daily, standard operations. (2) The initial calibration exercise accurately characterized the response of the analytical system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of a statistically significant difference between the mean of the normalized data collected at the beginning of a 6-month analysis period and the overall mean of all analyses over 6 months strongly suggests the following: (1) The analytical system was relatively constant in performance in spite of daily tuning, calibration, and other daily, standard operations. (2) The initial calibration exercise accurately characterized the response of the analytical system.…”
Section: Resultsmentioning
confidence: 99%
“…Homogeneous gas-phase reactions of gaseous pollutants including organics, nitrogen oxides, and sulfur dioxide lead to the formation of condensible vapors and, ultimately, to the production of secondary aerosols. Gas-to-particle conversion is also thought to lead to aerosols in the remote marine environment where dimethyl sulfide (DMS), which is excreted by phytoplankton, reacts to form sulfuric acid and methanesulfonic acid (MSA) (1). Numerous studies have documented the formation of secondary aerosols through homogeneous gas-phase reactions of gaseous pollutants (2-4), but a quantitative understanding of the gas-to-particle conversion has not yet been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Patterson (10) has recently summarized the current state of development of thermoionic ionization detectors for use in gas chromatography; Maraño et al (11), Ramstad and Nichelson (12), and Cooper et al (13) have reported on the application of such detectors in the analysis of nitriles. The flameless TID employed in the present study was a Dani Model 68/20, which works with a Rb2Si04 glass bead afixed to a heated platinum wire.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…Merck Index•, Merck & Co., Inc.: Rahway, NJ, 1989; p 758. (12) Wallingford, R. A.; Ewing, A. G. Anal. Chem.…”
mentioning
confidence: 99%